2018
DOI: 10.1007/s10876-018-1348-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the “Activation” of the Nanocluster [HxPMo12O40⊂H4Mo72Fe30(O2CMe)15O254(H2O)98-y(EtOH)y] for Low Temperature Growth of Carbon Nanotubes

Abstract: (FeMoC), was the first molecular catalyst precursor (pro-catalyst) that promised controlled growth of carbon nanotubes (CNTs); however, temperatures in excess of * 900°C or the addition of excess iron were required as catalyst promoters for CNT growth. To understand these disappointing results the ''activation'' of FeMoC for CNT growth was studied by systematic investigation of H 2 gas concentration and growth temperature. The pathway for ''activation'' of FeMoC occurs through the sufficient reduction of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 47 publications
5
7
0
Order By: Relevance
“…The increase in growth temperature appears to provide a more favorable growth environment for carbon nanotubes. This transition in CNT growth at temperatures >900 • C agrees with prior work using FeMoC [16,17,23,24,44], suggesting that FeMoC has a temperature dependent activation mechanism for CNT growth [26]. Product yield for the growth temperature experiments is shown to increase when the growth temperature is increased from 700 • C to 900 • C. This is followed by a decrease in product yield when increasing the growth temperature to 1000 • C. This growth temperature relationship with product yield likely arises from the temperature dependent behavior of the kinetics of hydrocarbon decomposition.…”
Section: Variation Of Growth Temperaturesupporting
confidence: 87%
See 2 more Smart Citations
“…The increase in growth temperature appears to provide a more favorable growth environment for carbon nanotubes. This transition in CNT growth at temperatures >900 • C agrees with prior work using FeMoC [16,17,23,24,44], suggesting that FeMoC has a temperature dependent activation mechanism for CNT growth [26]. Product yield for the growth temperature experiments is shown to increase when the growth temperature is increased from 700 • C to 900 • C. This is followed by a decrease in product yield when increasing the growth temperature to 1000 • C. This growth temperature relationship with product yield likely arises from the temperature dependent behavior of the kinetics of hydrocarbon decomposition.…”
Section: Variation Of Growth Temperaturesupporting
confidence: 87%
“…This transition in CNT growth at temperatures >900 °C agrees with prior work using FeMoC [16,17,23,24,44], suggesting that FeMoC has a temperature dependent activation mechanism for CNT growth [26]. Product yield for the growth temperature experiments is shown to increase when the growth temperature is increased from 700 °C to 900 °C.…”
Section: Variation Of Growth Temperaturesupporting
confidence: 85%
See 1 more Smart Citation
“…The product was refluxed in EtOH for 12 h and a dark green solution was collected. [20,24,25]. In brief, 1.00 g (5.03 mmol) of iron (II) chloride tetrahydrate was dissolved in 75 mL of Millipore water in a 500 mL round-bottom flask containing a stir rod.…”
Section: [Hxpmo12o40h4mo72fe30(o2cme)15o254(h2o)90−y(etoh)y] (1) Synmentioning
confidence: 99%
“…We have previously employed the large molecular cluster, [HxPMo12O40H4Mo72Fe30(O2CMe)15O254(H2O)98−y(EtOH)y] (1) [20] (Figure 1), as a catalyst precursor for the growth of carbon nanotubes (CNTs) [21][22][23][24][25]. During our study, we demonstrated that the composition of the catalyst, and the subsequent ability to grow CNTs, was highly dependent on the activation step, which involved reduction at elevated temperatures [24]. This, in turn, led to a detailed study of the kinetics of the reduction from 1 to the active catalyst species [26].…”
Section: Introductionmentioning
confidence: 99%